Respuesta :
Answer:
12x
Step-by-step explanation:
When you break the bracket, you will get:
= 14x - 2x + y - y
= 14x -2x
= 12x
Hope this help :3
Simplified form of expression is 12x
What is linear expression?
An algebraic expression of constants and variables with highest power one is known as linear expression.
How to solve?
Given : 14x - (2x - y) - y
Multiplying -1 from (2x -y)
= 14x - 2x + y - y
Adding and subtracting terms with similar variables
= 12x
To learn more about simplifying expressions visit :
https://brainly.com/question/1280754
#SPJ2